Money buys happiness in constant payments - López-Rousseau, Alejandro; Córtes Silva, Cristián (Revista de Psicología, 2019)
Nobody doubts that money buys at least some happiness. The question is how and why. This study answers that question. Some university students were asked to imagine they would win a one million dollars prize payable in five yearly payments, and to choose what plan –an increasing, constant, or decreasing payments plan– would make them happier. They were also asked why, and what would they spend the money on. The findings suggest that money buys happiness in constant payments because of better expense management on basic goods. And they provide converging evidence that money promotes happiness when spent on others.